A STUDY ON THE IMPACT OF DISCOUNT AND ODD-EVEN PRICING STRATEGY ON THE PURCHASE INTENTIONS OF OTT MEDIA USERS IN INDIA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
Covid-19 pandemic has changed the Indian TV  and video market. OTT platforms saw a sudden  increase in popularity and subsequent increase in  subscription. However, the recent announcement  of price cut in Netflix’s subscription packages  once again brings to the foray the effect of  pricing on purchase behavior. Following Netflix,  other OTT players also announced similar  subscription offers. Present research aims to  study of the effect of odd pricing (or 9-ending  pricing) and discount pricing on the purchase  intention. It is intended to answer questions  on the extent to which pricing policies affect  purchase of media products and how customers  perceive the value-based pricing concept of OTT  players. Research findings indicate that there is  a positive relationship between pricing policies  and purchase intention of OTT subscription  packages. The results also show that the pricing  strategies affect the purchase of media products  and perceived price fairness has a positive impact  on purchase intention.
Keywords: Pricing; OTT; Purchase intentions; Value based pricing; Price fairness